A novel multi-port SEPIC converter with grid-tie system for hybrid power generation - Supriya Jayaprakash; Rajashekar Jangam Siddamallaiah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
As the load demand continues to rise on a daily basis, there will be an increased requirement for sources of renewable energy.Â  When compared to the building of an entire power system, the cost of distributed generation, also known as DG, is significantly lower, which makes it a useful tool for fulfilling the demand for electricity. However, these DG are built utilizing renewable energy, which by their very nature is intermittent in its output. As a result, hybrid power generation, which draws power from a variety of sources, is employed to meet the demand for electricity. There are many multiport converters available but they use more number of components which causes complexity and increase in size. And as there are many devices there are possibility stability in the power generation may take time. A brand-new multi-port single ended primary inductor converter (MP-SEPIC), sometimes known as an MP-SEPIC, is proposed in this article. Connecting the photovoltaic (PV), wind, and fuel cell systems is done in order to evaluate the performance of the MP-SEPIC converter. A comparison is made between the standard multi-port boost converter and the suggested MP-SEPIC, the MATLAB simulation is carried out for the purpose of validating the proposed system.